Bortezomib-Induced Pulmonary Toxicity: A Case Report and Review of Literature - Prakash Kharel; Deekchha Uprety; Abhinav B. Chandra; Yirui Hu; Anuradha Avinash Belur; Ajay Dhakal (Case Reports in Medicine)
Bortezomib, a proteasome inhibitor, is an established therapy against multiple myeloma. Bortezomib-induced lung injury, although not appreciated during the introductory time of the medication, has now been highlighted in multiple case reports. The objective of this study is to report a case of bortezomib-induced lung injury, review current literature, and perform exploratory analysis.